SPIRITUAL AND SENSUOUS DIMENSIONS IN ARUN JOSHI’S THE LAST LABYRINTH (International Journal of Food and Nutritional Sciences, 2022)
Arun Joshi’s The Last Labyrinth was awarded the Sahitya Academy Award for its excellent theme. The spiritual and sensuous dimensions are interwoven with great intensity in this novel. The novel, The Last Labyrinth is considered as an outstanding contribution of Indian English Literature for its search for a meaning in human existence. Joshi in his novels focused not only on socio-political issues but he has touched the deep sensitive layers of human beings. Joshi’s works also reflects the strong influence of Indian spiritual ideology. The protagonist in the novel, The Last Labyrinth, is a millionaire industrialist and his incessant urge towards life is depicted in this novel. This paper analyses the struggles of the characters to seek peace and their surrender towards spiritual existence.